EXTERNAL AND INTERNAL EGG QUALITY CHARACTERISTICS OF INDIGENOUS SIRUVIDAI, ASEEL AND WHITE LEGHORN CHICKENS - D. Gandhimathi; P. Muthusamy; R. Richard churchil; K. Thilak Pon Jawahar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to evaluate external and internal egg quality characters of three chicken breeds/ ecotypes namely, indigenous Siruvidai, TANUVAS Aseel and White Leghorn.  A total of 180 eggs (120 eggs from Siruvidai chicken, 30 eggs from TANUVAS Aseel and 30 eggs from White Leghorn) were subjected to this study. The weight, length, width and surface area of White Leghorn eggs were significantly (P